Dose-Escalated Stereotactic Body Radiation Therapy for Prostate Cancer: Quality-of-Life Comparison of Two Prospective Trials - Quon, Harvey C.; Musunuru, Hima Bindu; Cheung, Patrick; Pang, Geordi; Mamedov, Alexandre; D’Alimonte, Laura; Deabreu, Andrea; Zhang, Liying; Loblaw, Andrew (Frontiers in Oncology, 2016)
Introduction The optimal prostate stereotactic body radiation therapy (SBRT) dose-fractionation scheme is controversial. This study compares long-term quality of life (QOL) from two prospective trials of prostate SBRT to investigate the effect of increasing dose (NCT01578902 and NCT01146340). Material and Methods Patients with localized prostate cancer received SBRT 35 or 40 Gy delivered in 5 fractions, once per week. QOL was measured using the Expanded Prostate Cancer Index Composite (EPIC) at baseline and every 6 months. Fisher’s exact test and generalized estimating equations were used to analyze proportions of patients with clinically significant change and longitudinal changes in QOL. Results 114 patients were included, 84 treated to 35 Gy and 30 treated to 40 Gy. Median QOL follow-up was 56 months (interquartile range [IQR] 46-60) and 38 months (IQR 32-42), respectively. The proportion of patients reporting clinically significant declines in average urinary, bowel, and sexual scores were not significantly different between dose levels, and were 20.5 vs. 24.1% (p=0.60), 26.8 vs. 41.4% (p=0.16), and 42.9 vs. 38.5% (p=0.82), respectively. Similarly, longitudinal analysis did not identify significant differences in QOL between treatment groups. Conclusion Dose-escalated prostate SBRT from 35 to 40 Gy in 5 fractions was not associated with significant decline in long-term QOL.